Geographic views of the city: methodological proposals in teaching geography - Silva, Gabriel de Miranda Soares; Oliveira, Meire Rose dos Anjos (Revista Ensino de Geografia (Recife), 2020)
In this article we propose to discuss the city as a guide in Geography teaching-learning process, starting from the perception of urban agents, looking for a geographical sight from high school students about the city and their daily lives. We present different methodological proposals for the teaching of Urban Geography, among these activities we highlight: the field activity and class, the making of photographic records and finally, the making and application of a board game. Thus, students were able to understand the city where they live, the name of the historical agents and the process of formation of the socio-spatial characteristics of the city of Várzea Grande, MT. We consider that the activities beacon the proposal for a socio-constructivist education based on the students' knowledge combined with the concepts of Geography, giving meaning to Geography at and from school